The Relationship between Urbanization, CO2 Emissions, Economic Growth and Energy Consumption in Nigeria - Akorede, Yusuf Fatai; Afroz, Rafia (International Journal of Energy Economics and Policy, 2020)
The first objective is to examine the trend analysis of the relationship between energy consumption and carbon dioxide on one hand and the trend analysis of the relationship between economic growth and CO2 emission on the other hand. The second objective is to determine the long-run relationship and direction of causality among the variables. To achieve this objective, the study used Granger causality test and the results shows a bi-directional causality between urban population and Energy consumption. The third objective is to examine the impact of urbanization, energy consumption, economic growth on carbon dioxide emission in Nigeria. To achieve this, the study employed Autoregressive distributed lag (ARDL) test approach. The results show that in the short run, energy consumption and the previous lag of economic growth have a positive and significant impact on carbon dioxide emission in Nigeria. Only urban population has a negative but significant impact on CO2 emission in Nigeria. In the long run however, urbanization is still statistically significant but negative while energy consumption and economic growth still has a positive and significant impact on CO2 emission. The major reason is that the bulk of the country’s energy consumption is from non-renewable means. Thus, the study recommend appropriate measures and mitigation policies needs to be put in place to reduce the damage on the environment and to prevent further destruction. Keywords: Urbanization, CO2 emission, economic growth, energy consumption, ARDL JEL Classifications: Q43, Q53, O47 DOI: https://doi.org/10.32479/ijeep.9355